EXPLORING THE ENTREPRENEURIAL INTENTION OF GENERATION Y PEOPLE IN THAILAND - Li, Cheng-Lung; Ngamvimutteyaporn, Yurika (International Journal of Application on Economics and Business, 2023)
The main purpose of this study is to analyse the factors affecting and exploring entrepreneurial intention of generation Y people in Thailand with particular attention to demographics, personal planned behaviours, and contextual factors, those factors will be the key tools that may encourage entrepreneurship. This study based on interview the person who born in 1980 to 1997 called generation Yers. The results showed they have a high expectation of being a self-employee rather that working in a well-known organisation and be able to understand the idea how these young entrepreneurs identify business opportunities and overcome challenges through self-attitudes toward unforeseen failure in business. Yers believe that they are the huge wave of movement to challenge and develop a globalisation throughout creativity and innovation. This study also shown the result of relationship among demographics, personal planned behaviours, and other contextual details that are the main key tools were the determinants of Thai entrepreneurial intention.